Kebiasaan Tidak Memakai Celana/Rok Panjang Merupakan Faktor Risiko Kejadian Demam Berdarah Dengue (Studi pada Siswa SD di Kota Semarang) - Mada Gautama; Suharyo Hadisaputro; Mateus Sakundarno Adi; Muchlis Achsan Udji Sofro; Suhartono Suhartono (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background : Dengue Haemorrhagic Fever is still remains a health problem in Indonesia, especially in the city of Semarang. Based on data for the year 2014 from the Semarang City Health Office, DBD many experienced by the age group 1-14 years as many sufferers of1,065 (65%), in children ages 6 – 12 years old recorded 336 sufferers (ITP 20.6%). Some protective factors that affect mosquito bite incident DBD in children is wearing pants/skirt length, the use of repellent, the installation of netting on the bed, the installation of ram mosquitoes.Methods : The design was a case control study. The total sample was 160 children (80 children per group) selected by proportional random sampling with due regard to inclusion and exclusion criteria. Data analysis was bivariate with chi-square test and multivariatelogistic regression.Results : There are two variables that may prevent the incidence of Dengue HaemorraghicFever in school children, that is wearing pants/long skirts at home (p = 0.003; Or = 2,781;95% CI = 1,412-5,476), installation of ram mosquitoes in the windows (p = 0,018; Or =2,462; 95% CI = 1,166-5,200).Conclusion : The occurrence of DHF in children can be prevented by wearing pants/long skirts at home, and the installation of ram mosquitoes in the windows home. Probability to experience the occurrence of Dengue Haemorrhagic Fever is 78,72%.